ECG classification using wavelet transform and Discriminant Analysis - Farah Nur Atiqah, Francis Abdullah; Fazly, Salleh; Rosli, Besar (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/